PRAKTIK KERJA ADIL DAN KESEIMBANGAN PEKERJAAN-HIDUP DI INDUSTRI BERKEKUATAN TINGGI - Yohan Purnawan; Yeni Trisna Purba; Peronika Sari BR Tarigan (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
This study aims to examine the relationship between fair work practices and work-life balance among employees in high-intensity industries in Indonesia, as well as their impact on organizational outcomes. The research employed a quantitative correlational design. Data were collected through online questionnaire surveys, supported by semi-structured interviews and focus group discussions, with a total sample of 300 professional employees who had worked for at least one year in technology, finance, consulting, advertising, and startup sectors. Fair work practices were measured using the Organizational Justice Scale (Colquitt, 2001) covering four dimensions (distributive, procedural, interactional, and informational justice), while work-life balance was measured using the Work-Life Balance Scale (Fisher-McAuley et al., 2003). Data analysis was conducted using Structural Equation Modeling (SEM), and mediation effects were tested using bootstrapping. The results indicate that fair work practices are implemented at a moderate-to-high level (mean = 4.25), whereas work-life balance remains at a moderate level (mean = 3.65). Fair work practices have a positive and significant effect on work-life balance (β = 0.48; p < 0.001). Moreover, both fair work practices and work-life balance positively and significantly influence job satisfaction, organizational commitment, and performance. Work-life balance also significantly mediates the relationship between fair work practices and all organizational outcomes (mediation effects range from 0.173 to 0.197). These findings highlight the importance of fair work practices as an organizational resource to improve employee well-being and performance in high-intensity work environments.